Antibiotic-Loaded Gold Nanoparticles: A Nano-Arsenal against ESBL Producer-Resistant Pathogens - Syed Mohd Danish Rizvi; Amr Selim Abu Lila; Afrasim Moin; Talib Hussain; Mohammad Amjad Kamal; Hana Sonbol; El-Sayed Khafagy (Pharmaceutics, 2023)
The advent of new antibiotics has helped clinicians to control severe bacterial infections. Despite this, inappropriate and redundant use of antibiotics, inadequate diagnosis, and smart resistant mechanisms developed by pathogens sometimes lead to the failure of treatment strategies. The genotypic analysis of clinical samples revealed that the rapid spread of extended-spectrum β-lactamases (ESBLs) genes is one of the most common approaches acquired by bacterial pathogens to become resistant. The scenario compelled the researchers to prioritize the design and development of novel and effective therapeutic options. Nanotechnology has emerged as a plausible groundbreaking tool against resistant infectious pathogens. Numerous reports suggested that inorganic nanomaterials, specifically gold nanoparticles (AuNPs), have converted unresponsive antibiotics into potent ones against multi-drug resistant pathogenic strains. Interestingly, after almost two decades of exhaustive preclinical evaluations, AuNPs are gradually progressively moving ahead toward clinical evaluations. However, the mechanistic aspects of the antibacterial action of AuNPs remain an unsolved puzzle for the scientific fraternity. Thus, the review covers state-of-the-art investigations pertaining to the efficacy of AuNPs as a tool to overcome ESBLs acquired resistance, their applicability and toxicity perspectives, and the revelation of the most appropriate proposed mechanism of action. Conclusively, the trend suggested that antibiotic-loaded AuNPs could be developed into a promising interventional strategy to limit and overcome the concerns of antibiotic-resistance.